In vitro evaluation of the anti-proteolytic and cross-linking effect of mussel-inspired monomer on the demineralized dentin matrix. (August 2021) - Li, Kang; Zhang, Zhongni; Sun, Yuhong; Yang, Hongye; Tsoi, James Kit Hon; Huang, Cui; Yiu, Cynthia Kar Yung
Abstract: Objectives: To evaluate the anti-proteolytic and cross-linking effect of N -(3, 4-dihydroxyphenethyl)methacrylamide (DMA) on the demineralized dentin matrix in vitro . Methods: Four experimental solutions were selected: 50% ethanol/water solution (Control); 1, 5, and 10 mmol/L DMA dissolved in 50% ethanol/water solution. Sound human molars were sectioned to produce dentin beams with dimension of 1×1×6 mm. The dentin beams were demineralized with 10% phosphoric acid for 8 h to remove the apatite. The demineralized specimens were randomly separated into four groups and immersed in the four experimental solutions for 1 h. After the treatment, the ultimate tensile strength (UTS), loss of dry mass and the release of hydroxyproline by storing the treated specimens in 0.1 mg/mL collagenase solution for 24 h were assessed. The swelling ratio of another ten specimens from each group were evaluated. The interaction between DMA with dentin matrix was observed under Field Emission Scanning Electron Microscopy (FESEM). UTS data was analyzed by two-way ANOVA followed by Tukey test, and the other data was analyzed by one-way ANOVA followed by Tukey test (α = 0.05). Results: The two-way ANOVA factors, different solutions ( p < 0.001), collagenase degradation ( p < 0.001) and their interactions ( p < 0.001) all significantly affected the UTS. The 10 mM DMA treatment significantly decreased the percentage of loss of dry mass, release of hydroxyproline and swelling ratio of demineralized dentin matrix compared to other treatment groups ( p < 0.05). The FESEM observation depicted that with increasing concentration of DMA, the structure of dentin matrix was protected and the porosity within dentin collagen network was decreased. Conclusions: The treatment by 10 mM DMA/ethanol solution for 1 hour is capable of enhancing the mechanical properties of demineralized dentin matrix against collagenase degradation and may be clinically useful to improve the durability of hybrid layer. Clinical Significance: The 10 mM DMA/ethanol primer may offer an alternative choice for dentists to strengthen the mechanical properties of demineralized dentin matrix and resist its degradation by collagenase.